1981
DOI: 10.1113/jphysiol.1981.sp013970
|View full text |Cite
|
Sign up to set email alerts
|

Form and function of dorsal horn neurones with axons ascending the dorsal columns in cat.

Abstract: SUMMARY1. Extracellular and intracellular recordings were made from dorsal horn neurones sending their axons through the dorsal columns in cats anaesthetized with chloralose and paralysed with gallamine triethiodide.2. Seventeen neurones were injected with horseradish peroxidase through the intracellular micro-electrode, recovered from the histological material and shown to send their axons into the dorsal columns.3. The cells had axonal conduction velocities of 30-47 ms-1; excitatory receptive fields that usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 29 publications
(26 reference statements)
6
63
1
Order By: Relevance
“…While a small minority of units with spatially separate excitatory fields has been previously reported among samples of unidentified dorsal horn neurones (Devor & Wall, 1976;Pubols & Goldberger, 1980;Brenowitz & Pubols, 1981) these have always been located on the most proximal areas of the limb. Indeed, apart from previous studies of this system in the chloralose-anaesthetized cat (Brown & Fyffe, 1981;Brown et al 1983), there are no reports of dorsal horn neurones with complex receptive fields of the type that have been observed for PSDC units with input from glabrous skin. Several previous studies of PSDC neurones in the pentobarbitone-anaesthetized cat have failed to detect inhibitory input (Uddenberg, 1968;Angaut-Petit, 1975;Lu et al 1983), but inhibitory fields have been reported in about half of a sample of PSDC neurones recorded in the chloralose-anaesthetized cat (Brown et al 1983).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…While a small minority of units with spatially separate excitatory fields has been previously reported among samples of unidentified dorsal horn neurones (Devor & Wall, 1976;Pubols & Goldberger, 1980;Brenowitz & Pubols, 1981) these have always been located on the most proximal areas of the limb. Indeed, apart from previous studies of this system in the chloralose-anaesthetized cat (Brown & Fyffe, 1981;Brown et al 1983), there are no reports of dorsal horn neurones with complex receptive fields of the type that have been observed for PSDC units with input from glabrous skin. Several previous studies of PSDC neurones in the pentobarbitone-anaesthetized cat have failed to detect inhibitory input (Uddenberg, 1968;Angaut-Petit, 1975;Lu et al 1983), but inhibitory fields have been reported in about half of a sample of PSDC neurones recorded in the chloralose-anaesthetized cat (Brown et al 1983).…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports of the receptive field arrangements of PSDC neurones recorded in pentobarbitone-anaesthetized animals have stressed their similarity with neurones of the SCT (Uddenberg, 1968;Angaut-Petit, 1975;Lu et al 1983), while experiments on chloralose-anaesthetized animals suggest a considerably more complex receptive field organization (Brown & Fyffe, 1981 ;Brown et al 1983). The present observations confirm that the majority of PSDC neurones, at least in the chloralose-anaesthetized preparation, have complex receptive fields which differ in their organization from those of identified neurones of the SCT (Hongo, Jankowska & Lundberg, 1968;Brown & Franz, 1969;Brown, Koerber & Noble, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations